Localization of the genes for the two chlorophyll a-conjugated polypeptides (mol. wt. 51 and 44 kd) of the photosystem II reaction center on the spinach plastid chromosome - Westhoff, Peter (1983)
A core particle of the water-oxidizing photosystem II reaction center has been prepared from stacked spinach thylakoid membranes by a procedure involving extraction with the non-ionic detergent dodecyl-β-D-maltoside and centrifugation in sucrose gradients. The protein-pigment complex consists of at least four polypeptide species: two components with mol. wts. of 51 and 44 kd which are conjugated with chlorophyll a and β-carotene, the herbicide-binding protein of mol. wt. 32 kd and cytochrome b 559 (11 kd). The genes for the 51-and 44-kd polypeptides have been located on the circular 150-kbp spinach plastid chromosome. They were identified by hybrid-selection mapping, in vitro transcription-translation of recombinant DNAs and specific antisera which were used to characterize the translation products. The plastid chromosome carries one uninterrupted copy for each of these genes in its large single-copy region. The gene for the 51-kd protein (which probably bears the P(680) reaction center chlorophyll a) is located in close proximity to the gene for cytochrome b6, and some 70 kbp away from the gene for the `32-kd' herbicide-binding protein of the reducing side of photosystem II. The gene for the 44-kd protein is situated halfway between these two genes adjacent to the gene for the P(700) chlorophyll a apoprotein of the photosystem I reaction center. Both photosystem II genes are transcribed into discrete RNA species in the same direction but from the opposite strand as the gene for the `32-kd' protein.